Photomask Technology 2008 2008
DOI: 10.1117/12.801883
|View full text |Cite
|
Sign up to set email alerts
|

32nm 1-D regular pitch SRAM bitcell design for interference-assisted lithography

Abstract: In double patterning lithography (DPL) layout decomposition for 45nm and below process nodes, two features must be assigned opposite colors (corresponding to different exposures) if their spacing is less than the minimum coloring spacing. 5, 11, 14However, there exist pattern configurations for which pattern features separated by less than the minimum coloring spacing cannot be assigned different colors. In such cases, DPL requires that a layout feature be split into two parts. We address this problem using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Fig. 19 (b), (c) and (d) shows the layout for the Array 0, Array 1-2 and Array 3, respectively in 32nm technology [27]. All the layouts include the synapse array, neuron, input data buffer, row decoder, column decoder and sense amplifier circuits.…”
Section: Simulation Results and Layoutmentioning
confidence: 99%
“…Fig. 19 (b), (c) and (d) shows the layout for the Array 0, Array 1-2 and Array 3, respectively in 32nm technology [27]. All the layouts include the synapse array, neuron, input data buffer, row decoder, column decoder and sense amplifier circuits.…”
Section: Simulation Results and Layoutmentioning
confidence: 99%
“…For physical layout design and evaluation, 1-D Gridded design rules [41] were used to compare the area of GNTRAM cell with Gridded 8T SRAM cell [42] in 16nm technology node. Regular 6T CMOS SRAM scaled to 16nm technology node was also used for benchmarking.…”
Section: Methodology and Benchmarkingmentioning
confidence: 99%
“…PTM interconnect RC models based on scaled interconnect dimensions were used in conjunction with the PTM transistor models for power and performance evaluation of GNTRAM using HSPICE. For physical layout design and area evaluation of GNTRAM, 1-D gridded design rules [Bencher et al 2009] were used as shown in Table II. For benchmarking against CMOS, 16nm Gridded 8T SRAM cell [Greenway et al 2008] was used, since this SRAM design utilizes the same grid-based design used in GNTRAM. Regular 6T CMOS SRAM scaled to 16nm technology node was also used for benchmarking.…”
Section: Methodology and Benchmarkingmentioning
confidence: 99%